PEMIKIRAN HUKUM IMAM ABU HANIFAH DAN IMAM AL-SYAFI’I TENTANG ZAKAT MADU - Abu Azam Al Hadi (Al Hikmah: Jurnal Studi Keislaman, 2014)
Zakat is one of the ordinances of Allah in using Allah property makes property as a means of life of all mankind, and therefore should be directed to the common good. Someone who has met the terms of which are obliged to fulfill their zakat. Once the importance of worship zakat, so the set of sanctions against those who are reluctant to give charity. Zakat is also very important for increasing the economic life of the people and their welfare. Honey is one of the gift of God to His servants that contain lots of subtances of food, medicines from the juice. It means that honey bees are out of the stomach is a gift from Allah SWT. Honey is a liquid produced by bees chewy from various sources and plant juice has one function, namely as a drug for humans.According to Imam Abu Hanifah that the honey shall be issued zakat, as is obligatory for all the results that came out of the ground, provided that bees do not nest in the kharajiyah land, because the kharajiyah land already levied taxes, in accordance with the provision that the two obligations can not be both contained in one property by reason of the same one. But if the honey is in the ‘usyriyah land, then it must be taken the zakat, as well as when bees nest in the woods or mountains. Imam al-Shafi'i has a different argument with Imam Hanafi. He argues that the honey is a type of property that can not be used as an object of charity, and he further agrees that it is free of zakat of honey, because the goods are collected zakat must have strong proofs either sunnah or atsar.